THE INFLUENCE OF LAVENDER AROMATHERAPY TO DECREASE OF PAIN ON PATIENT POST-SECTIO CAESAREA (SC) OPERATIONS IN HOSPITAL ISLAMIC SAKINAH MOJOKERTO - Enny Virda Yuniarti; IMA RAHMAWATI (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2020)
Background Every surgery is always associated with an incision trauma for patients happened various complaints and symptoms.One of the most common complaints is a pain. One of the non-pharmacological therapy can be used to reduce the pain of postoperative patients section Caesarea by using relaxation techniques of lavender aroma therapy. Objective The research purpose was to prove the influence of lavender aromatherapy on the decrease in pain of post operative patients section caesarian (sc). MethodsThe researchwas aPre-Experimental study with One Group Pretest-Posttest approach. The population of this study were all postoperative patients section Caesarea with a sample of 25 respondents taken using purposive sampling. The data source uses primary data with instances of pain scale NRS (Numerical Rating Scale). Data analysis used Wilcoxon Signed Ranktest. The result of this research obtained before giving thearoma of lavender therapy on apostoperative patient of section Caesarea as many as 13 respondents had mild pain and there was a change of pain scale after providingsmell of lavender therapy six respondents had mild pain. Wilcoxon statistic test result Ranktest obtained p-value (Asymp.Sing.2- tailed) = 0,002 (p <0,05), found the influence of aromatherapy of lavender to decrease thepain of postoperative patient of section Caesarea (sc) in RSI Sakinah Mojokerto. ConclusionAroma lavender therapy can decrease pain because the content of the lavender is linalool acetate that can relax and relax the working system of muscles and muscles that tense